2015
DOI: 10.3168/jds.2013-7704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of core body temperature, time of day, and climate conditions on behavioral patterns of lactating dairy cows experiencing mild to moderate heat stress

Abstract: Cattle show several responses to heat load, including spending more time standing. Little is known about what benefit this may provide for the animals. Data from 3 separate cooling management trials were analyzed to investigate the relationship between behavioral patterns in lactating dairy cows experiencing mild to moderate heat stress and their body temperature. Cows (n=157) were each fitted with a leg data logger that measured position and an intravaginal data logger that measures core body temperature (CBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
156
2
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(186 citation statements)
references
References 30 publications
17
156
2
11
Order By: Relevance
“…Along with the increase in THI by 1 unit between the W and H periods, there was observed a decrease in LTD by 38 min/d in the cubicles, while in the manure alleys it increased by 15 min/d. The declines in lying bouts' length demonstrated by Allen et al (2015) and Kanjanapruthipong et al (2015) caused by an increase in THI were confirmed by LTH calculated in different areas of the barn. However, it is characteristic that despite very unfavourable conditions in the barn during the period between 12:00 pm and 04:00 pm, the cows staying in the feeding alley returned and lay down in the cubicles.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Along with the increase in THI by 1 unit between the W and H periods, there was observed a decrease in LTD by 38 min/d in the cubicles, while in the manure alleys it increased by 15 min/d. The declines in lying bouts' length demonstrated by Allen et al (2015) and Kanjanapruthipong et al (2015) caused by an increase in THI were confirmed by LTH calculated in different areas of the barn. However, it is characteristic that despite very unfavourable conditions in the barn during the period between 12:00 pm and 04:00 pm, the cows staying in the feeding alley returned and lay down in the cubicles.…”
Section: Discussionsupporting
confidence: 54%
“…In order to cool their bodies, cows increase their respiration rates and consume less feed during hot weather, which in turn causes a decline in milk production (West 2003;Tousova et al 2017). However, high temperatures and high relative humidity make this process difficult and the cow's body temperature increases (Allen et al 2015). This may result in impaired thermoregulation and heat stress (Rhoads et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In the other side, when those cows were in the sunny part of the paddock, they preferred to ruminate while lying compared with ruminating while standing (34.1 v. 11.5 min) probably to increase exposed surface of their body in contact with the ground and enhance conduction of heat loss to the environment. Cows' preference for standing posture was already noticed by Soriani et al (2013) and Allen et al (2015) but not by Schütz et al (2014).…”
Section: Discussionmentioning
confidence: 86%
“…This was not the case in the present study as cows had more than 10 m 2 each of available shade. On the other hand, Allen et al (2015) observed that at a core body temperature equal to 38.9°C, there was a 50% likelihood that a cow would be standing, which highlights the importance of this behavior in the cooling of animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of high temperatures and high relative humidity interferes with this process and the body temperature of the cows rises (Allen et al 2015), sometimes resulting in inadequate regulation of the cow’s body temperature and the occurrence of heat stress (Rhoads et al 2009). …”
Section: Introductionmentioning
confidence: 99%